Practical management of riociguat in patients with pulmonary arterial hypertension - Halank, Michael; Grünig, Ekkehard (Therapeutic advances in respiratory disease, 2019)
Riociguat is one of several approved therapies available for patients with pulmonary arterial hypertension (PAH). Treatment should be initiated and monitored at an expert center by a physician experienced in treating PAH, and the dose adjusted in the absence of signs and symptoms of hypotension. In certain populations, including patients with hepatic or renal impairment, the elderly, and smokers, riociguat exposure may differ, and dose adjustments should therefore be made with caution according to the established scheme. Common adverse events are often easily managed, particularly if they are discussed before starting therapy. Combination therapy with riociguat and other PAH-targeted agents is feasible and generally well tolerated, although the coadministration of phosphodiesterase type 5 inhibitors (PDE5i) and riociguat is contraindicated. An open-label, randomized study is currently ongoing to assess whether patients who do not achieve treatment goals while receiving PDE5i may benefit from switching to riociguat. In this review, we provide a clinical view on the practical management of patients with PAH receiving riociguat, with a focus on the opinions and personal experience of the authors.
Gesehen am 15.01.2020